Urban Fashion Formations in the Twenty‐First Century: Weberian Ideal Types as a Heuristic Device to Unravel the Fashion City. (30th October 2020) - Casadei, Patrizia; Gilbert, David; Lazzeretti, Luciana
Abstract: In recent years, local governments and academic researchers have drawn increasing attention to the idea of the fashion city as a strategic factor for urban economic growth. In addition to renowned fashion capitals, second‐tier cities of fashion have proliferated, giving rise to a large heterogeneity of centres of production, design, consumption and culture. Despite its rising popularity, however, the concept of the fashion city is still weakly codified, and only simplistic tool‐kit strategies have been adopted to transform cities into contemporary fashion hubs. Drawing upon Weber's ideal‐type approach, this intervention develops an analytical framework for thinking about the diverse nature of fashion's relation with cities. The search for the elusive singular fashion city is replaced by three ideal types—the 'manufacturing fashion city', the 'design fashion city' and the 'symbolic fashion city'—which can be used as a heuristic device to trigger debate about the distinctive characteristics of fashion centres and speculate about future developmental pathways. The essay stimulates critical reflection on the different kinds of positioning that fashion takes in urban economies and the developmental pathways of different forms of fashion city formations.